Increasing Students' Civic Knowledge Through the Application of the Cooperative Learning Model of Make a Match Type Assisted by Wordwall Media - Cahyati, Suci; Sumardi, Lalu; Sawaludin, Sawaludin; Yuliatin, Yuliatin (Jambura Journal Civic Education, 2025)
The purpose of this study was to evaluate the effectiveness of the implementation of cooperative learning model type Make A Match mediated by Wordwall in improving the understanding of civic concepts of seventh grade students at SMP Negeri 2 Praya. This classroom action research took place in two cycles, in each cycle there are several stages which include planning, implementation, observation, and reflection. The subjects of this study were all students of class VII totalling 30 people consisting of 17 women and 13 men. Data collection was done through observation sheets and formative tests. Descriptive quantitative data analysis was used to process the data obtained. The results showed an increase in the percentage of students who reached the minimum completeness criteria (KKM) by 33.33% from cycle I to cycle II, from 10% to 43.33% in cycle I, then significantly increased to 76.66% in cycle II. In addition, the average value of student learning outcomes also experienced a significant increase of 14.97% from 57.66% in the initial condition to 72.63% in cycle I, and continued to increase to 85.74% in cycle II. Based on the findings of this study, it can be concluded that the application of cooperative learning model of Make A Match type by utilising Wordwall media is proven to be effective in improving the understanding of civic concepts of seventh grade students at SMP Negeri 2 Praya.